(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This article examines the development of students’ historical knowledge on the basis of Mahmudkhoja Behbudiy’s pedagogical views, interpreting it as a pressing socio-pedagogical issue under the conditions of globalization. The study identifies superficial acquisition of historical knowledge, indifference to national history, and the weak development of historical thinking as strategic risk factors for higher education, and substantiates the methodological potential of the Jadid legacy in addressing these challenges. Behbudiy’s understanding of education as a “force that awakens the nation,” his interpretation of history as the “mirror of the nation,” and his ideas on accelerating social progress through reforming schools and madrasas are analyzed as a conceptual foundation for strengthening the educational and social value of history as an academic discipline. The article explains that the Jadid pedagogical principles—teaching in connection with real life, rejecting rote memorization, orienting learning toward analysis, comparison, and reasoned conclusions, and ensuring harmony between national and universal values—are methodologically consistent with contemporary competency-based, learner-centered, activity-based, and constructivist approaches. It is concluded that integrating Behbudiy’s pedagogical ideas into history education can enhance students’ national self-awareness, civic stance, social engagement, moral resilience, and both critical and historical thinking, while also activating effective social mechanisms for shaping historical consciousness and national memory.